Downregulation of XIST ameliorates acute kidney injury by sponging miR‐142‐5p and targeting PDCD4. Issue 11 (29th April 2020) - Tang, Bo; Li, Weiliang; Ji, Tingting; Li, Xiaoying; Qu, Xiaolei; Feng, Linhong; Zhu, Yingchun; Qi, Yinghui; Zhu, Chun; Bai, Shoujun
Abstract: Acute kidney injury (AKI) is a common kidney disease that markedly affects public health. To date, the roles of long noncoding RNA XIST in AKI are poorly understood. Here, we investigated the biological functions of XIST in AKI. We observed that XIST expression increased in patients with AKI and HK‐2 cells stimulated by CoCl2 . In addition, a rat AKI model induced by ischemia–reperfusion was established. Tumor necrosis factor‐α, interleukin‐6, and cyclooxygenase‐2 messenger RNA expression were induced in vivo; moreover, XIST expression was upregulated. Knockdown of XIST significantly repressed CoCl2 ‐triggered injury in HK‐2 cells. However, microRNA (miR)‐142‐5p, a downstream target of XIST, was downregulated in AKI. miR‐142‐5p was repressed by XIST and miR‐142‐5p could inhibit CoCl2 ‐induced injury in HK‐2 cells. Moreover, PDCD4 expression was significantly increased in AKI. PDCD4 was predicted to be the target of miR‐142‐5p. Subsequently, loss of PDCD4 was able to retard injury in HK‐2 cells exposed to CoCl2. Thus, we suggest that XIST regulates miR‐142‐5p and PDCD4, and it has the potential to function as a biomarker in therapeutic strategies for AKI. Abstract : Long noncoding RNA XIST was significantly increased in acute kidney injury (AKI) and reduction of MBNL1‐AS1 obviously enhanced proliferation, reduced cell apoptosis of AKI. Dual‐luciferase reporter assay showed XIST was able to sponge miR‐142‐5p and raise the PDCD4 to promote AKI progression.